Breast Sarcomas: Rare but Challenging Entity for Diagnosis - Khemani, Rashmi; Murthy, Sudha S; K, Naidu C; Fonseca, Daphne; K, Suseela; B, Vishal Rao; Pasam, Mohan Krishna; KVVN, Raju; T, Subramanyeshwar Rao; A, Krishnam Raju (Annals of Pathology and Laboratory Medicine, 2020)
Background: Breast sarcomas are extremely rare, can be primary or secondary, pose a high risk of recurrence with an overall poor prognosis. Primary breast sarcomas constitute < 1% of all primary breast malignancies and less than 5% of all sarcomas. Sarcomas arising in phyllodes tumors account for < 6 % of all phyllodes tumors. The most common subtype of both primary and secondary sarcoma is angiosarcoma. Methods: This was a retrospective study of patients diagnosed as sarcoma of breast (excluding malignant phyllodes and metaplastic carcinoma) during the period from January 2016 to July 2019. The demographic and clinical features were noted from the medical records. The details of gross specimens (grossed in strict accordance with CAP protocols) were noted. The haematoxylin and eosin-stained slides along with immunohistochemistry (IHC) (pan cytokeratin, calponin, vimentin, SMA, CD117, Ki 67, desmin, CD10, CK5/6, EMA, p63, CD34, CD56, myogenin, CD99, p16, S100, BCL2, CD31, caldesmon and CD68) were reviewed and categorized according to WHO (2019) criteria. Result: The median age of patients was fifty years. There were fourteen breast sarcomas including one arising in phyllodes tumor during the study period. These included undifferentiated pleomorphic sarcoma (4), liposarcoma (2), myxofibrosarcoma (2), angiosarcoma (2), one each of leiomyosarcoma, rhabdomyosarcoma, fibrosarcoma and stromal sarcoma. Despite using a wide panel of IHC markers, 4/14 (28.57%) sarcomas were classified as undifferentiated pleomorphic sarcoma. Conclusion: Primary breast sarcomas are rare tumors and pose diagnostic challenge. It is important to categorize these entities in view of the differing biologic behavior and molecular profiles. Morphology along with IHC is important for diagnosis, treatment and prognosis.